Homeownership and parenting practices: Evidence from the community advantage panel - Grinstein-Weiss, Michal (2010)
This study examines whether there is a significant relationship between homeownership and engaged parenting practices among low- and moderate-income households. Using analytic methods which account for selection effects and clustering, we test whether homeownership can act as a protective factor against parental disengagement from children. Controlling for individual characteristics, analyses demonstrate that homeowners are more likely than renters to demonstrate engaged parenting behaviors such as organizing structured activities for their children. While renters are more likely to read to their children, the children of homeowners spend less time watching television and playing video games. Implications for low-income housing policy are discussed in light of these findings.